Fruit and vegetable biodiversity for nutritionally diverse diets: Challenges, opportunities, and knowledge gaps - Harris, Jody; Zonneveld, Maarten van; Achigan-Dako, Enoch G.; Bajwa, Babar; Brouwer, Inge D.; Choudhury, Dhrupad; Jager, Ilse de; Steenhuijsen Piters, Bart de; Dulloo, Mohammad Ehsan; Guarino, Luigi; Kindt, Roeland; Mayes, Sean; et al. (Elsevier, 2022)
Planetary health brings together intrinsically linked issues of human health and natural systems. This paper reviews evidence of how agrobiodiversity underpins dietary diversity for current human populations in the context of fruits and vegetables, and ways to maintain and improve these for future generations.